2014
DOI: 10.1007/s00125-014-3305-x
|View full text |Cite
|
Sign up to set email alerts
|

Incretin, insulinotropic and glucose-lowering effects of whey protein pre-load in type 2 diabetes: a randomised clinical trial

Abstract: Aims/hypothesis Since protein ingestion is known to stimulate the secretion of glucagon-like peptide-1 (GLP-1), we hypothesised that enhancing GLP-1 secretion to harness its insulinotropic/beta cell-stimulating activity with whey protein pre-load may have beneficial glucose-lowering effects in type 2 diabetes. Methods In a randomised, open-label crossover clinical trial, we studied 15 individuals with well-controlled type 2 diabetes who were not taking any medications except for sulfonylurea or metformin. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
134
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(152 citation statements)
references
References 10 publications
14
134
3
1
Order By: Relevance
“…For example, the consumption of whey protein with a high glycemic meal decreased postprandial serum glucose in patients with diabetes (Jakubowicz et al., 2014). We recruited obese yet young, apparently healthy participants that exhibited fairly normal postprandial metabolic and vascular responses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the consumption of whey protein with a high glycemic meal decreased postprandial serum glucose in patients with diabetes (Jakubowicz et al., 2014). We recruited obese yet young, apparently healthy participants that exhibited fairly normal postprandial metabolic and vascular responses.…”
Section: Discussionmentioning
confidence: 99%
“…We found no significant differences in glycemic responses between the trials involving nonfat milk and those with the control drink that included the same amount of protein. These results confirm previous findings that at least some of the beneficial effects of milk on glycemic responses can be attributed to its protein quantity (Akhavan et al., 2010, 2014; Ballard et al., 2013; Elwood et al., 2010; Fekete et al., 2016; Gannon et al., 1992; Jakubowicz et al., 2014; Manders et al., 2014). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…
Abbreviations
CCKCholecystokinin GLP-1 Glucagon-like peptide-1To the Editor: We read with interest the Short Communication from Jakubowicz et al, published recently in Diabetologia [1]. The authors reported that acute administration of 50 g whey protein, in liquid form, 30 min before a high carbohydrate breakfast, substantially reduced postprandial glycaemia as compared with placebo in patients with type 2 diabetes, and there were concomitant increases in both glucagon-like peptide-1 (GLP-1) and insulin.
…”
mentioning
confidence: 99%